ESR STUDY OF CUCL2 ADSORBED ON A CHEMICALLY-MODIFIED SILICA-GEL SURFACE WITH BENZIMIDAZOLE MOLECULE - Dias, N. L.; Gushikem, Y. (Elsevier B.V., 1995)
The ESR spectrum of CuCl2 adsorbed onto a silica gel surface chemically modified with the benzimidazole molecule showed that the surface complex has an octahedral symmetry with tetragonal distortion. The measured ESR parameters were g(parallel to) = 2.287, g(perpendicular to) = 2.062, A(parallel to) = 153 G and superhyperfine splitting A(N) = 15 G. The fit of the theoretical expressions to the experimental data was very reasonable. The effective spin orbit coupling constant for Cu2+ was reduced from its normal free ion value of lambda = -828 cm(-1) by as much as 30%. This reduction of lambda is normal in the solid state and in frozen solution complexes.